Prevalence of Mycoplasma genitalium in men with urethritis and in high risk asymptomatic males in Tel Aviv: a prospective study. (February 2017) - Gottesman, Tamar; Yossepowitch, Orit; Samra, Zmira; Rosenberg, Shoshana; Dan, Michael
We sought to investigate the prevalence of Mycoplasma genitalium, Chlamydia trachomatis, Neisseria gonorrhoeae, and Trichomonas vaginalis in men presenting to a sexually transmitted infection (STI) clinic, with special attention to M. genitalium, its occurrence in Israeli patients, coinfections, and risk factors. In a cross-sectional study, 259 men were successively enrolled in the Tel Aviv Levinsky Clinic for STIs between November 2008 and November 2010. There were 118 men with urethritis and 141 high-risk men without symptoms. M. genitalium, C. trachomatis, N. gonorrhoeae, and T. vaginalis were detected using nucleic acid amplification tests. Demographic characteristics and risk factors were documented. The overall prevalence of infection with M. genitalium, C. trachomatis, N. gonorrhoeae, and T. vaginalis, were 6.6%, 12.7%, 23.1%, and 0%, respectively. Prevalences in men with urethritis were 11.9%, 22%, and 49%, for M. genitalium, C. trachomatis, and N. gonorrhoeae, respectively. Prevalences in men without symptoms were 2.1%, 5.0%, and 1.4%, for M. genitalium, C. trachomatis, and N. gonorrhoeae, respectively. Co-infections were found only in symptomatic individuals, in whom 5.9% were infected concomitantly with C. trachomatis and N. gonorrhoeae, and 2.5% had dual infection with M. genitalium and N. gonorrhoeae . N. gonorrhoeae, C. trachomatis, and M. genitalium were significantly more prevalent in patients with urethritis. M. genitalium was significantly more prevalent in the heterosexual population than in homosexual males. To conclude, we have found that M. genitalium infection is associated with urethritis in Israeli men, and more so in the heterosexual population. Testing men for M. genitalium as a cause of non-gonococcal urethritis is warranted, particularly because of its poor response to doxycycline and possible failure of azithromycin.